The Pedagogical Functions of Arts and Cultural-Heritage Education with in Online Art Galleries and Musuems. Issue 1 (March 2015) - Zhao, Pei; Sintonen, Sara; Kynäslahti, Heikki
Digital museums and arts galleries have become popular in museum education and management. Museum and arts galleries website is one of the most effective and efficient ways. Google, a corporation specializing in Internet-related services and projects, not only puts high-resolution arts images online, but also uses augmented-reality in digital art gallery. The Google Art Project, Google's production, provides users a platform in appreciating and learning arts. With the virtual reality, recently after Google Art Project, more and more countries released their own museum and arts gallery websites, like British Paining in BBC, and FINNA in Finland. Pedagogical function in these websites is one of the most important functions. In this paper, we use Google Art Project and FINNA as the case studies to investigate what kinds of pedagogical functions exist in these websites. Finally, this paper will give the recommendation to digital museums and websites development, especially the pedagogical functions development, in the future.